Estado, industrialização e os espaços de acumulação das Multilatinas - Santos, Leandro Bruno [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
A partir de meados dos anos 1990, instituições internacionais, imprensa especializada em assuntos econômicos e trabalhos acadêmicos trataram de enfatizar o aumento considerável dos fluxos de Investimentos Diretos Estrangeiros (IDE) oriundos de países subdesenvolvidos. Este fenômeno apresenta, historicamente, diferentes ciclos e alterações de importância entre as regiões e os países. Com o seu aprofundamento, porém, as assimetrias espaciais – centro e periferia – são redefinidas e são produzidas novas espacialidades, particularmente a relativização das relações Norte-Sul e o fortalecimento das relações materiais Sul-Sul. O principal objetivo que norteia esta tese é a compreensão do papel desempenhado pelos principais grupos multinacionais latino-americanos, Multilatinas, originários de quatro países (Argentina, Brasil, Chile e México), no processo de concentração e centralização em escala mundial, com o destaque, principalmente, à atuação do Estado, aos ramos econômicos, às formas de inserção internacional, às escalas espaciais de acumulação e às diferentes frações de capitais...

From de mid of 1990, international institutions, specialized press in economic affairs and academic works tried to emphasize the considerable increase of Foreign Direct Investment Flows (FDI) from underdeveloped countries. This phenomenon shows, historically, different cycles and changes of importance between regions and countries. With its deepening, however, spatial asymmetries –Center and Periphery- are reset and produced new spatialities, particularly the relativization of North-South relations and the strengthening of South-South material relations. The main purpose that guides this thesis is the understanding of the role played by the major multinational business groups in Latin America, Multilatinas originating in four countries (Argentina, Brazil, Chile and Mexico), in the process of concentration and centralization on a worldwide scale, with the highlight, mainly, to the role of the State, to the economic branches, to the forms of international insertion, to the spatial accumulation scales, and to the different fractions of capitals. In the historical dialectic relationship between the external impulses and the geographical and historical condition of each Latin American socio spatial formation, under the mediation of the states, were internalized the processes of production and circulation of capital and engendered different Capitalism... (Complete abstract click electronic access below)
Keywords: Geografia; Espaço em geografia; Globalização; Desenvolvimento econômico; America Latina; Geography